Biofilm Production and Antimicrobial Resistance in Clinical Pseudomonas aeruginosa Isolates: An Integrated Analysis with Clinical and Therapeutic Implications - Mohamed Salem Eshlak; Fathallah Ali Salim; Mohamed Abdulsalam Shallouf; Emad Mohammed Elzain (African Journal of Advanced Pure and Applied Sciences, 2025)
Pseudomonas aeruginosa is a major opportunistic pathogen in healthcare settings, notorious for biofilm-mediated antimicrobial resistance (AMR) that significantly complicates clinical management. This cross-sectional study comprehensively analyzed biofilm formation and AMR profiles in 80 clinical P. aeruginosa isolates from diverse infection sites at Misurata Medical Centre (2023–2024). Biofilm production was assessed using Congo Red Agar (CRA), Crystal Violet Tube (CVT), and Microtiter Plate (MTP) assays. Antimicrobial susceptibility was determined via Clinical and Laboratory Standards Institute (CLSI) disc diffusion. The MTP assay demonstrated superior sensitivity, detecting 65% strong biofilm producers, with a significant association between strong biofilm production and multidrug resistance (MDR, 72.4%, p < 0.001). Resistance was highest to levofloxacin (45%), ceftazidime (42.5%), and imipenem (28.7%). These data reinforce global trends and highlight biofilm-targeting therapies as urgent clinical priorities. The study advocates routine biofilm detection and innovative anti-biofilm interventions to combat MDR P. aeruginosa infections.